Case Report: Local Anesthesia Round Window Plugging and Simultaneous Vibrant Soundbridge Implant for Superior Semicircular Canal Dehiscence - Mignacco, Giulia; Salerni, Lorenzo; Bindi, Ilaria; Monciatti, Giovanni; Cerase, Alfonso; Mandalà, Marco (Frontiers in Neurology, 2020)
The aim of the present study is to report the outcomes of round window reinforcement surgery performed with the application of a Vibrant Soundbridge middle ear implant (VSB; MED-EL) in a patient with superior semicircular canal dehiscence syndrome (SSCD) who presented with recurrent vertigo, Tullio phenomenon and Hennebert’s sign, bone conduction hypersensitivity, and bilateral moderate to severe mixed hearing loss. Vestibular evoked myogenic potentials (VEMPs) and high resolution computed tomography (HRCT) confirmed bilateral superior semicircular canal dehiscence while this was not seen at magnetic resonance imaging. The surgical procedure was performed in the right ear as it had poorer vestibular and auditory symptoms, hearing threshold, HRCT and VEMP findings. With local-assisted anesthesia, round window reinforcement surgery (plugging) with perichondrium was performed with simultaneous positioning of a VSB on the round window niche. At 1 and 3 months follow-up after surgery, VSB-aided hearing threshold in the right ear improved to mild, and loud sounds did not elicit either dizziness or pain in the patient.